Evaluasi sensori natural flavor ”pengganti MSG” dari limbah kulit dan tulang ikan tuna (Thunnus sp.) - Febi Mulfiza; Lia Handayani; Rulita Maulidya (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
There are several compounds in flavoring that give food's special aroma, taste or characteristics, such as Monosodium Glutamate (MSG). MSG is a synthetic chemical that if consumed in excess can have a bad impact on health. MSG can be replaced with natural flavors that have a similar taste. Fish skin and bones have a high content of calcium and phosphorus, in addition to minerals, proteins and volatile compounds, so they can be used as natural spices as consumer awareness of natural flavors increases. This study aims to determine the effect of the comparison of tuna fish bone and skin (Thunnus sp.) as a natural flavor on organoleptics. The research method used is an experimental laboratory method, this study used two different types of waste and each treatment was carried out 3 times, The type of waste used was tuna bones and skin. With a ratio of water and tuna bone and skin waste, namely: 1:2 (b/v), 1:3 (b/v), 1:4 (w/v). Nonparametric data were analyzed using the Kruskall-Wallis method, the Mann-Whitney test if there was a significant difference, followed by the Bayes test to determine the best treatment. Flavoring was analyzed by 30 trained and semi-trained panelists. Based on the results of the organoleptic test, the best flavor was found in sample E with a taste preference value of 6.82±0.068, aroma 6.89±0.11, color 7.19±0.02, and texture 7.14±0.08.